Put a bet on it: Can self-funded commitment contracts curb fitness procrastination? - Devon Spika; Linnea Wickström Östervall; Ulf-G. Gerdtham; Erik Wengström (Lund University, School of Economics and Management, Department of Economics, 2023)
This paper investigates the use of self-funded commitment contracts to support individuals in achieving their goals of increased physical activity. We compare the effect of soft (non-incentivised) commitment contracts with hard (incentivised) contracts using a randomised experiment with 1629 members of a large gym in Stockholm, Sweden. We find a significant positive impact of being offered a hard contract on monthly visits to the gym and the probability of meeting one's contract goal. Hard and soft commitment contracts increase gym visits by 21% and 8%, respectively, relative to the control group. Trait self-control is negatively associated with the likelihood of accepting a contract and accepting to add stakes. The effect of soft and hard commitment contracts does not, however, differ by trait self-control. Importantly, we find that the effects of both hard and soft contracts were greatest among participants who reported exercising the least at baseline. Our experiment explores the use of a completely self-funded and highly scalable intervention. Our experimental design allows us to shed light on the importance of hard penalties in designing commitment contracts.
Keywords: I12; D03; C93; 330; Gym attendance; Incentives; Commitment contract; Self-control